Pengembangan Kurikulum Berbasis Keterampilan Dalam Menghadapi Tuntutan Kompetensi Abad 21 - Bustanul Arifin; Abdul Mu'id (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2024)
Education plays a pivotal role in shaping individuals to meet the demands of the ever-evolving 21st-century competencies. This study delves into the development of a skill-based curriculum tailored to address the challenges posed by the competencies required in the 21st century. Utilizing a qualitative research approach, we identified essential skills through literature reviews, expert consultations, and interviews with stakeholders. The curriculum development process entailed collaborative efforts among education experts, teachers, and industry professionals. The implementation phase, executed in various educational institutions, facilitated a comprehensive evaluation through methods such as classroom observations, interviews, and analyses of examination results. Findings underscore a noteworthy enhancement in students' critical thinking, creativity, communication, and collaboration skills. The discussion segment examines the successful adaptation of the curriculum to meet the needs of the contemporary workforce. Furthermore, it identifies challenges encountered during implementation, including teacher resistance and resource constraints. The conclusion emphasizes the critical necessity of integrating 21st-century skills into the curriculum and underscores collaborative efforts among stakeholders as imperative for the curriculum's success. This research provides profound insights into the significance of crafting a relevant curriculum to prepare students for the dynamic challenges of the future.